2020
DOI: 10.1039/d0ra08741f
|View full text |Cite
|
Sign up to set email alerts
|

Porous MOF-808@PVDF beads for removal of iodine from gas streams

Abstract: Porous millimeter-sized MOF-808@PVDF composite beads with ultrahigh iodine adsorption capacity for capture of radioiodine from gas streams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In contrast, much lower adsorption capacities were obtained with ionic MOFs (i.e., Zn-BTeC and MIL-127), and they were found to be only slightly dependent on the nature of the compensating ion present in the pores. Such predicted values are still higher than the best reports, such as in Zr-based MOF-808 at 80 °C (2.18 g·g −1 ) without water [ 70 ], or MOF-808 covered by poly(vinylidene fluoride) (1.42 g·g −1 ) [ 72 ]. It should be noted that a comparison with experimental data is difficult due to the scarcity of the experimental reports.…”
Section: Resultsmentioning
confidence: 76%
“…In contrast, much lower adsorption capacities were obtained with ionic MOFs (i.e., Zn-BTeC and MIL-127), and they were found to be only slightly dependent on the nature of the compensating ion present in the pores. Such predicted values are still higher than the best reports, such as in Zr-based MOF-808 at 80 °C (2.18 g·g −1 ) without water [ 70 ], or MOF-808 covered by poly(vinylidene fluoride) (1.42 g·g −1 ) [ 72 ]. It should be noted that a comparison with experimental data is difficult due to the scarcity of the experimental reports.…”
Section: Resultsmentioning
confidence: 76%
“…The X-ray photoelectron spectroscopy (XPS, Thermo Scientific Escalab 250Xi, Waltham, MA, USA) of the beads was also measured to analyze the elemental chemical bonding states. The procedure of iodine adsorption by DUT-68@Alginate beads was carried out according to the previous work [ 13 , 17 ]. Briefly, sealed bottles with 20 mg beads in a glass vial and 200 mg solid iodine were kept at 358 K in the oven and weighted at different times.…”
Section: Methodsmentioning
confidence: 99%
“…[ 20–22 ] Furthermore, many studies have confirmed that MOFs can be efficiently incorporated into organic polymer films to form mixed matrix‐membranes, self‐folding films, and other types of functional films. [ 23–27 ]…”
Section: Introductionmentioning
confidence: 99%